McDowall and Lynch Supplementary Data - McDowall, Philip; Lynch, Heather (Dryad Digital Repository, 2019)
Shapefile containing all 1,893,597 hexagonal cells, along with information on each cell's elevation, slope, cost-weighted distance to shore, flow accumulation, occupancy status (occupied vs unoccupied), and number of first-order neighbors. See Appendix S1 for further details.